1979
DOI: 10.1210/endo-104-5-1369
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Long Term Treatment with a Luteinizing Hormone-Releasing Hormone Agonist on the Pituitary-Gonadal Axis in Male and Female Rats

Abstract: Following previous observations of the potent antifertility effects of acute treatment with LHRH or its agonistic analogs in male and female rats, this study describes the effect of long term (up to 12 weeks) treatment with an LHRH agonist, [D-Ala6, des-Gly-NH210]LHRH ethylamide (LHRH-A), on testicular and ovarian gonadotropin receptor levels and function in the rat. Treatment of adult male rats with 100 ng LHRH-A every third day led to a progressive decrease of testis, seminal vesicle, and prostate weight up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(35 citation statements)
references
References 22 publications
0
34
0
1
Order By: Relevance
“…These effects were initially attributed to gonadotropin-induced depletion of LH receptors and desensitization of testicular steroidogenesis to subsequent hormonal stimulation (7,11,26 (28). In contrast serum testosterone levels in adult male rats treated daily with GnRH-A do not fall until 1.5-4 days after treatment (9), even though testicular gonadotropin receptors are markedly reduced within 10 hr after a single injection (13).…”
Section: Discussionmentioning
confidence: 99%
“…These effects were initially attributed to gonadotropin-induced depletion of LH receptors and desensitization of testicular steroidogenesis to subsequent hormonal stimulation (7,11,26 (28). In contrast serum testosterone levels in adult male rats treated daily with GnRH-A do not fall until 1.5-4 days after treatment (9), even though testicular gonadotropin receptors are markedly reduced within 10 hr after a single injection (13).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to be the case for such widely diverse hormones as LH [8], luteinizing hormone-releasing hor mone [4,9], growth hormone [10], insulin [22] and thyrotrophin-releasing hormone [7], The phrase down-regula tion is frequently used to describe the negative effects of a hormone on its receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that treatment with GnRH agonists desensitizes pituitary gonadotropin secretion and down-regulates gonadal gonadotropin receptors [1,2]. On the other hand, it was reported that GnRH infusion suppressed hCG-induced ovulation in rabbits [20], suggesting direct ovarian inhibition of GnRH and its analogues in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term administration of gonadotropin-releasing hormone (GnRH) agonists suppresses the pituitary-gonadal functions and induces hypogonadotropic hypogonadism both in humans and experimental animals [1,2]. These agonists thus have been widely used for the treatment of sex hormone-dependent disorders such as endometriosis, uterine leiomyoma, prostatic cancer and precocious puberty [3,4].…”
Section: Introductionmentioning
confidence: 99%